A Fluorescence-Detected Coordination-Induced Spin State Switch - Kurz, Hannah; Schoetz, Konstantin; Papadopoulos, Ilias; Heinemann, Frank Wilhelm; Maid, Harald; Guldi, Dirk Michael; Koehler, Anna; Hoerner, Gerald; Weber, Birgit (Journal of the American Chemical Society, 2021)
The response of the spin state to in situ variation of the coordination number (CISSS) is a promising and viable approach to smart sensor materials, yet it suffers to date from insensitive detection. Herein, we present the synthetic access to a family of planar nickel(II) complexes, whose CISSS is sensitively followed by means of fluorescence detection. For this purpose, nickel(II) complexes with four phenazine-based Schiff base-like ligands were synthesized and characterized through solution-phase spectroscopy (NMR and UV-vis), solid-state structure analysis (single-crystal XRD), and extended theoretical modeling. All of them reveal CISSS in solution through axial ligating a range of N- and O-donors. CISSS correlates nicely with the basicity of the axial ligand and the substitution-dependent acidity of the nickel(II) coordination site. Remarkably, three out of the four nickel(II) complexes are fluorescent in noncoordinating solvents but are fluorescence-silent in the presence of axial ligands such as pyridine. As these complexes are rare examples of fluorescent nickel(II) complexes, the photophysical properties with a coordination number of 4 were studied in detail, including temperature-dependent lifetime and quantum yield determinations. Most importantly, fluorescence quenching upon adding axial ligands allows a "black or white", i.e. digital, sensoring of spin state alternation. Our studies of fluorescence-detected CISSS (FD-CISSS) revealed that absorption-based CISSS and FD-CISSS are super proportional with respect to the pyridine concentration: FD-CISSS features a higher sensitivity. Overall, our findings indicate a favored ligation of these nickel(II) complexes in the excited state in comparison to the ground state.
CRIS-Team WoS Importer:2021-03-26